MKSAP for students : (American College of Physicians, 2000)
(Clerkship Directors in Internal Medicine) Consists of a collection of patient-centered self-assessment questions and their answers. Each question has a critique with the correct answer, an explanation of the answer, and a bibliography. This learning text is intended for third-year internal medicine students. Softcover. DNLM: Clinical Medicine--Problems and Exercises.